THE TECHNOLOGY OF DEVELOPMENT OF PROFESSIONAL AND COMMUNICATIVE CHARACTERISTICS OF FUTURE FOREIGN LANGUAGE TEACHERS - Dilafruz Baxriddinova; Shoira Ismailova; Munisxon Rajabova; Shakhzoda Uljayeva (The Bioscan, 2024)
In this article, we will discuss some specific features of the development of professional and communicative competences of future foreign language teachers. In addition, the professional-communicative character of a person is an indicator of the spiritual wealth of a culture of thought, a common component for all types of professional competence (general, special, psychological, etc.) as a means of personal development.